Food safety and hygiene knowledge of professional food handlers employed in university canteens: a questionnaire-based survey in Thessaloniki, Greece - Lazou, T (Journal of the Hellenic Veterinary Medical Society, 2025)
The burden of foodborne illnesses is an important public health issue even in modern societies with upgraded food safety systems. The role of food handlers in the safety of food at the time of consumption is critical with elevated implications in the case of professionals in food service settings for whom the lack of food safety knowledge has been recognised as a major barrier to following safe food-handling practices. This study assessed the self-reported food safety and hygiene knowledge of professional food handlers employed in university canteens operating in Thessaloniki, Greece, with the objective to provide novel insights on the level of corresponding awareness and knowledge gaps. In total, 26 food handlers employed in 15 university canteens voluntarily completed a self-administered anonymous questionnaire containing 15 multiple-choice questions on topics relevant to food hygiene and foodborne pathogens. The obtained average knowledge score was 72.6%. Most respondents correctly replied to the general hygiene questions relevant to the presence of microorganisms on kitchen surfaces and utensils (69 – 100%) but only a marginal majority (54%) accurately recognised bleach sanitizer as potential chemical hazard, for which a statistically significantly correlation (P-value = 0.033) with previous food hygiene training was detected. Regarding the temperature-related hygiene questions, less than two thirds of the respondents were aware of the maximum allowed operating temperature of refrigerators in terms of food safety and the actual effect of freezing on harmful bacteria in food. With the unique exception of Salmonella (92%), merely around one third of the food handlers (27 – 35%) accurately recognised the most common food vehicles of foodborne bacterial pathogens of high public health relevance, such as Campylobacter, Listeria monocytogenes and Staphylococcus aureus. The results of this study provide insights on the level of food safety and hygiene awareness among Greek professional food handlers in university canteens and highlight relevant knowledge gaps, which call for targeted and tailored training initiatives based on actual needs.